2010
DOI: 10.1111/j.1462-2920.2010.02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Depicting more accurate pictures of protistan community complexity using pyrosequencing of hypervariable SSU rRNA gene regions

Abstract: Initial environmental pyrosequencing studies suggested highly complex protistan communities with phylotype richness decisively higher than previously estimated. However, recent studies on individual bacteria or artificial bacterial communities evidenced that pyrosequencing errors may skew our view of the true complexity of microbial communities. We pyrosequenced two diversity markers (hypervariable regions V4 and V9 of the small-subunit rDNA) of an intertidal protistan model community, using the Roche GS-FLX a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(173 citation statements)
references
References 30 publications
3
168
0
2
Order By: Relevance
“…The number of OTUs decreased rapidly with increasing threshold distance from 0 to 10%, which might be attributed to inaccuracies during PCR and pyrosequencing (Supplementary Figure S1; Behnke et al, 2011;Quince et al, 2011). However, the number of OTUs stabilized from 10 to 30% of threshold distance, indicating that the threshold distances of 17-33% used for diversity analyses in this study rendered the analysis insensitive to such potential inaccuracies (Supplementary Figure S1; see the 'Materials and methods' section for details).…”
Section: Denitrifiers In Cryoturbated and Unturbated Peat K Palmer Et Almentioning
confidence: 97%
See 1 more Smart Citation
“…The number of OTUs decreased rapidly with increasing threshold distance from 0 to 10%, which might be attributed to inaccuracies during PCR and pyrosequencing (Supplementary Figure S1; Behnke et al, 2011;Quince et al, 2011). However, the number of OTUs stabilized from 10 to 30% of threshold distance, indicating that the threshold distances of 17-33% used for diversity analyses in this study rendered the analysis insensitive to such potential inaccuracies (Supplementary Figure S1; see the 'Materials and methods' section for details).…”
Section: Denitrifiers In Cryoturbated and Unturbated Peat K Palmer Et Almentioning
confidence: 97%
“…This approach is more reliable (that is, less sensitive to PCR and pyrosequencing noise, and thus less sensitive to an artifical inflation of diversity (Kunin et al, 2010)) than multiple alignments and/or clustering with complete linkage algorithms (Quince et al, 2009;Sun et al, 2009;Huse et al, 2010). Amplicon sequences obtained by pyrosequencing from defined template mixtures were essentially at most 10% dissimilar to template sequences due to PCR and pyrosequencing noise (Behnke et al, 2011;Quince et al, 2011). The threshold distances used to call OTUs in this study were 17-33%, which is substantially greater than the above-reported maximal PCR and pyrosequencing noise (Supplementary Figure S1).…”
Section: Sequence Filtering and Analysismentioning
confidence: 99%
“…If we exclude singletons from the data set, the curves showed more saturated trends at a range of 1000-20,000 reads. The OTUs showing low abundance (or consisting of a single read) could be rare species (Sogin et al 2006), while Behnke et al (2011) reported that singletons should be eliminated for reliable data interpretation. Thus, removal of singletons from data sets could be an appropriate way to avoid overestimation of ciliate diversity in despite of loss of few rare species.…”
Section: Discussionmentioning
confidence: 99%
“…Both V4 and V9 are considered suitable regions for biodiversity studies given their great variability and the combination of high and low entropy in these sections, which allows forgood primer binding (Behnke et al, 2011;Hadziavdic et al, 2014;Tanabe et al, 2016). They also have been widely used in molecular diversity studies, so the research community knows the advantages and limitations of both regions (AmaralZettler et al, 2009;Stoeck et al, 2010;Massana et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that this threshold might group species or even genus into the same OTU. However, in this way, it reduces the amount of singletons or artifactual OTUs and the consequent overestimation of rare diversity (Kunin et al, 2010;Behnke et al, 2011). To achieve our objective on finding unknown diversity, we opted to forgo fine taxonomical resolution.…”
Section: Clustering and Taxonomical Annotationmentioning
confidence: 99%